Analysis of the Influence Of Leadership Style And Job Satisfaction On Turnover Intention Through Job Stress At Customer Service (Frontline) PT. XXX Logistic Company In Jakarta - Hendra Gunawan; Erny Tajib (International Journal Of Humanities Education and Social Sciences (IJHESS), 2025)
The problem of this research was Turnover intention is a factor of discomfort experienced agent in a company. Turnover intention needs to get serious attention to the organization especially to leadership or manager so can applying leadership properly and improve job satisfaction to reduce job stress in the company.  The purpose of this research was the effect of leadership style and job satisfaction toward Turnover intention throught job stress at customer service (frontline) PT. XXX, Logistic Company in Jakarta.The methodology of this research was testing hypothesis. The data used were primary data collected from questionaire. The samples consisted of 164 customer service (frontline) PT. XXX Logistic Company in Jakarta, which were determined through purposive sampling method. The data were analyzed through Structural Equation Model (SEM) of AMOS version 23.0 for Windows.  The results of the study showed that there is a negative and significant influence between leadership style to work stress with estimate -0,343 and p-value 0,035. There is a negative and significant influence between job satisfaction to work stress with estimate -0,411 and p-value 0,016. There is a positive and significant influence of work stress on Turnover intention with estimate 0,781 and p-value  0,000 ., there is a negative influence of leadership style on the  Turnover intention with estimate -0,595 and p-value   0,000. There is a negative and significant influence between job satisfaction on the Turnover intention with estimate -0,369 and p-value 0,012.  Implication of this research is expected to managers can increase the determinants job stress itself for example by raising job satisfaction (salary, reward, job promotion) and applying force leadership proper and able to adjust with all the work situation